College readiness through an innovative concurrent enrollment program for underrepresented college bound students - Cevallos, Lynn. College Bridge; Webster, Kristin. California State University, Los Angeles; Cevallos, Pedro. College Bridge; Cevallos, Lynn; Webster, Kristin; Cevallos, Pedro (Center for Leadership Equity and Research)
This paper explores several key findings of the first three cohorts of the South Los Angeles Mathematics (SLAM) Project. The SLAM Project is a longitudinal study designed to learn the best practices to employ in order to increase college access and success for underrepresented students. In particular, this project tackles the mathematics remediation crisis directly in order to ensure that the students in the program begin their postsecondary careers in credit bearing courses and shorten their time to degree. The program is unique in its student selection and instructional model. Quantitative and qualitative results indicate significant effects of college level coursework on student perceptions, attitudes, and persistence rates.